2021
DOI: 10.7150/jca.54759
|View full text |Cite
|
Sign up to set email alerts
|

miR-369 inhibits Liver Cancer progression by targeting ZEB1 pathway and predicts the prognosis of HCC patients

Abstract: Increasing evidences show that microRNAs (miRNAs) are involved in the regulation of tumorigenesis, progression, recurrence and drug resistance of hepatocellular carcinoma (HCC). miR-369 works as a tumor suppressor in both lung cancer and thyroid cancer. However, the potential biological function of miR-369 in HCC is unknown. Herein, we for first found that miR-369 expression was downregulated in HCC tissues and predicted the poor prognosis of HCC patients. Forced miR-369 expression inhibited the proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Xie et al evidenced that miR-520a inhibits non-small cell lung cancer (NSCLC) progression through suppression of ribonucleoside-diphosphate reductase subunit M2 (RRM2) and Wnt signaling pathways [ 21 ]. Dong et al show that miR-369 expression is reduced in hepatocellular carcinoma (HCC) tissues [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al evidenced that miR-520a inhibits non-small cell lung cancer (NSCLC) progression through suppression of ribonucleoside-diphosphate reductase subunit M2 (RRM2) and Wnt signaling pathways [ 21 ]. Dong et al show that miR-369 expression is reduced in hepatocellular carcinoma (HCC) tissues [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis via antiapoptotic proteins (p53, bax, bcl-2, cyto C, and caspase 3), G1-phase cell cycle arrest via cell cycle regulators (cyclin D1 and CDK2/4/6) [26] Upregulated HDAC9 Epithelial-mesenchymal transition process activation; cellular stemness properties regulation [27] Non-coding RNAs miR-221/222 Enhanced cell growth via p27 regulation mTOR kinase regulation [28] miR-369 Zinc finger E-box binding homeobox 1 regulation [29] miR-3174 FOXO1 regulation [30] miR-383 IL-17 via STAT3 signaling pathway regulation [31] miR-361-5p CXCR6, VEGFA, or MAP3K9 regulation [32] miR-186 CSCs self-renewal [33] miR-186 Protein tyrosine phosphatase non-receptor type 11 regulation [34] miR-122 Tumor growth regulation [35] HOTAIR Proliferation, regulation of pluripotency, metastasis, and sensitivity to chemotherapeutics [36] HOTTIP Survival, tumor grade, and prognosis [37] Table 1. Cont.…”
Section: Downregulation Of Hdac5mentioning
confidence: 99%
“…Additional functional studies on a mouse model of liver cancer demonstrated that miR-221 overexpression stimulated the growth of tumorigenic murine hepatic progenitor cells [28]. Another study showed that miR-369, which targets zinc finger E-box-binding homeobox 1, is downregulated in liver fibrosis and liver cancer tissues, and can predict a poor prognosis in HCC patients [29]. Additionally, when miR-369 expression was restored, proliferation and metastasis of HCC cells in vitro and in vivo were inhibited.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Researches have revealed that circRNAs can regulate various cell biology through interacting with couples of microRNAs (miRNAs), that has been named as a competing endogenous RNA (ceRNA) mechanism [ 6 9 , 16 , 17 ]. miRNAs may regulate various functions through binding with the 3′ untranslated regions (UTR) of downstream target genes in HCC [ 18 21 ]. miR-1236-3p has been demonstrated to be involved with some digestive system cancers, such as gastric cancer [ 22 , 23 ] and colorectal cancer [ 24 ].…”
Section: Introductionmentioning
confidence: 99%